Resilience and Memory in the Poetics of Africadia: Sylvia D. Hamilton's And I Alone Escaped To Tell You - Cucarella-Ramon, Vicent (The Grove - Working Papers on English Studies, 2021)
Sylvia D. Hamilton’s collection of poems And I Alone Escaped To Tell You (2014) revolves around the vindication of the little remembered legacy of slavery of Africadians – George Elliott Clarke’s neologism to refer to African Canadians from the Maritime provinces – which acts as a metaphor of the silenced history of Black Canadians. To do so, Hamilton relies on memory work through the lens of resilience and, hence, participates in the recent post-trauma paradigm that is intent on highlighting resistance rather than victimhood. Thus, the resilient memory that emerges from the collection dismisses the position of victims for Africadians and, contrarily, focuses on the capacity to ‘bounce back’, to withstand historical adversities, to endure by being malleable and to adapt to conditions of crisis. Simply put, this resilient memory acts in the poems as the dignified exercise to keep on reinstating and vindicating the silenced history of Black Canada.